Creative Process Engagement Mediate the Relation Between Proactive Personality, Creativity Employee, and Innovation - Muhdiyanto Muhdiyanto; Ahyar Yuniawan; Fuad Mas’ud (Journal of International Conference Proceedings, 2021)
This study aims to explore the influences of proactive personality toward creativity and innovation through the process of creativity involvement from the perspective of Resource Dependence Theory.  This study was conducted on Small and Medium Enterprises (SMEs) in the Magelang area in the form of a survey.  The sample selection method in this study used with purposive sampling technique. The criteria used in this study are SMEs that have high creativity, such as children's toys, batik, and souvenirs, and have a minimum number of 10 employees. The number of samples in this study was 287 respondents.  The analytical tool to test the hypothesis in this study uses Structural Equation Modeling (SEM) with WarpPLS 7 software. The results show that proactive personality influences employees’ creativity through the involvement of the creative process.  Furthermore, creativity affects organizational innovation.